Construction of Islamic identity in the Lampung community leadership system through folk poetry - Jafar Fakhrurozi; Dadang Suganda; Lina Meilinawati Rahayu; Nani Darmayanti (Cogent Arts & Humanities)
This research examined the construction of Islamic identity and Lampung culture from the perspective community leadership through folk poetry. The research focused on analyzing oral folk poetry, specifically the wawancan and peppacur genres, which are integral to the cultural rituals of the Lampung people, especially in wedding ceremonies. The folk poetry is carried out from generation to generation. Until now, these traditional activities still take place in the lives of the community. This is a qualitative research, with Charles Sanders Peirce semiotic theory, elaborated by Peter Berger and Burhan Bungin’s social construction theory, used to analyze the texts of folk poetry. The findings highlight how folk poetry portrays various cultural symptoms and identities, with Islamic identity emerging as one of the most prominent. This identity is constructed through externalization, objectivation, and internalization, serving as a guiding value system for governance and societal practices.